MONITORING REAL-TIME ARUS DAN FUSE PADA SISTEM 220 V - Kiswantono, Agus (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The reliability of low-voltage power distribution systems greatly depends on protective devices such as the NH Fuse, which serves to disconnect circuits during overcurrent or short circuit events. In conventional systems, NH Fuse monitoring is still performed manually, causing delays in detecting faults and increasing the risk of extended outages and equipment damage. This study proposes the development of a web-based IoT monitoring system for NH Fuse performance in distribution substations. The system utilizes Hall Effect current sensors to measure current flow on the R, S, and T phases, processed by an ESP32 microcontroller and displayed via a local LCD screen and an online platform. The measured current values—4.3 A (R), 3.7 A (S), and 4.0 A (T)—indicate balanced loads across phases, which is essential for stable power distribution. The system is integrated with real-time notifications and a map-based fault tracking feature to enhance response time and maintenance efficiency. The use of IoT technology in this application enables continuous data transmission, improves system transparency, and facilitates faster decision-making during abnormal conditions. Results show that the system can effectively detect disturbances and immediately notify the monitoring team through the web platform, thus reducing the time needed for manual inspection. The implementation of this system can significantly improve the operational efficiency and reliability of power distribution infrastructure in line with modern smart grid requirements.